Aktivitas Dakwah Program Muslim Travelers Di NET TV Edisi Sleman Jawa Tengah Perspektif Analisis Holsti - Ulfah, Maria; Hadisaputra, Samian; Fahrurrozi, A. M. (Institut Attaqwa KH. Noer Alie Bekasi, 2024)
The human reasoning power that needs to be utilized and improved as a form of da'wah activity in this modern era does require support from communication media. Because the existence of communication media and information technology can provide speed, accuracy and practicality in carrying out da'wah activities so that they are conveyed quickly and precisely. As is the case with the Muslim Travelers program on NET TV which is a program traveling packaged creatively and innovatively, so that the presentation is adapted to today's modern times. The aim of this research is to answer, namely to find out how da'wah activities are carried out by the Central Java edition of the Muslim Traveler program, and what influence media communication from a holistic perspective has on da'wah activities. The type of research used is a descriptive qualitative approach with media content analysis methods according to Holsti. In this research, researchers used categories of da'wah activities in three parts, namely: morals, syari'ah and aqidah. and this media communication uses audio visuals or videos in the NET TV. Which is used as documentation that can be consumed by the public.